Mutualism effectiveness of a fungal endophyte in an annual grass is impaired by ozone - Ueno, Andrea Celeste (2016)
Ozone is an increasing tropospheric contaminant of climate change. Exposure to ozone may affect the symbiotic relationship between plants and beneficial microorganisms. In particular, the herbivore resistance mechanism conferred by fungal endophytes (defensive mutualism) may be affected, as any of the ozone-triggered effects (such as elicitation of defence mechanisms against biotrophic fungi or oxidative stress in the apoplastic space) may target the symbiont. Symbiotic and non-symbiotic Lolium multiflorum plants were exposed to ozone for two consecutive days (2 h per day), after which half were infested with 10 aphids (Rhopalosiphum padi). We measured variables related to performance of plants, the endophyte symbiont (alkaloids) and the herbivores. Aphid populations were smaller on symbiotic plants than in non-symbiotic plants in low-ozone conditions. However, this difference disappeared in exposed plants to high-ozone conditions. Under low-ozone conditions, structure of aphid populations on endophyte-symbiotic plants was characterized by a low number of nymphs and a high number of adults. This pattern was not observed with high-ozone exposure. Level of fungal alkaloids (lolines) was not affected by either ozone or herbivory. Results indicate that ozone impairs the grass-endophyte symbiosis without affecting production of alkaloids generally linked with aphids' response to endophyte presence. Since neither plant biomass nor alkaloid level were affected by ozone, other ozone-mediated mechanisms at molecular or biochemical level may underlie plant-herbivore interaction mediated by fungal endophytes. Thus, the mechanism behind this effect must be determined in future experiments.